2020
DOI: 10.1093/biolre/ioaa060
|View full text |Cite
|
Sign up to set email alerts
|

Tmprss12 is required for sperm motility and uterotubal junction migration in mice†

Abstract: Spermatozoa are produced in the testis but gain their fertilizing ability during epididymal migration. This necessary step in sperm maturation includes posttranslational modification of sperm membrane proteins that includes protein processing by proteases. However, the molecular mechanism underpinning this epididymal sperm maturation remains unknown. In this study, we focused on transmembrane serine protease 12 (Tmprss12). Based on multi-tissue expression analysis by PCR, Tmprss12 was specifically expressed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
2
19
0
Order By: Relevance
“…Indeed, our sperm morphology analysis showed that Zdhhc19 KO sperm had coiled and bent tails (Figure 4E). Under natural fertilization conditions, sperm must migrate through the UTJ, penetrate into the zona pellucida, and fuse to the oocyte [35]. Although spermatozoa with low motility may not reach UTJ, it is possible that they are capable of penetrating eggs in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, our sperm morphology analysis showed that Zdhhc19 KO sperm had coiled and bent tails (Figure 4E). Under natural fertilization conditions, sperm must migrate through the UTJ, penetrate into the zona pellucida, and fuse to the oocyte [35]. Although spermatozoa with low motility may not reach UTJ, it is possible that they are capable of penetrating eggs in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Given that Zdhhc19 KO mice were sterile yet with normal spermatogenesis, reduced sperm motility, and abnormal acrosome reaction, male infertility can be caused by failure of spermatozoa to migrate through the female uterotubal junction (UTJ) due to low sperm motility [35]. Alternatively, the sterility of Zdhhc19 KO mice may be attributed to defects in induced acrosome reaction and oocyte interaction/activation.…”
Section: Zdhhc19 Is Essential For In Vitro Fertilization In Micementioning
confidence: 99%
“…Endosomal cysteine proteases such as CTSB and CTSL are abundant in Leydig cells, Sertoli cells, seminal vesicles, the epididymis, and germ cells, and participate in the priming of S protein [ 23 , 24 ]. Expression of TMPRSS2, an important serine protease needed for viral entry into the host, is also evident in primordial germ cells and the acrosomal region of developing spermatogonia [ 6 , 7 ]. Finally as per the human protein atlas, neuropilin-1 (NRP-1) is expressed in Leydig cells and seminal vesicles.…”
Section: Reproductive Organs Expressing Entry Factors For Sars-cov-2mentioning
confidence: 99%
“…Hence, organs expressing these entry factors are at greater risk of COVID-19 mediated pathology and organ dysfunction. Studies have claimed the expression of these entry-factors in gonads and other accessory reproductive organs [ 6 , 7 ]. Therefore, it is possible that this virus might be able to invade reproductive organs and disrupt the reproductive health of infected individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Proteases also play important roles in reproduction, and several serine proteases and serine protease-like proteins are essential for normal fertility and therefore could be unique targets for nonhormonal male contraception (i.e., a male pill). For example, among the proteins essential for male fertility are the following: TMPRSS12, a testis-specific transmembrane serine protease required for sperm motility and uterotubal junction migration ( 21 ) and structurally similar to TMPRSS2; serine protease 55 (PRSS55), a glycosylphosphatidylinositol-anchored testis-specific serine protease that is necessary for sperm uterotubal junction migration and sperm–oocyte binding ( 22 , 23 ); serine protease 37 (PRSS37), a testis-specific inactive serine protease-like protein required for sperm uterotubal junction migration and fertilization ( 24 ); and ovochymase 2 (OVCH2), an epididymis-specific secreted serine protease required for maturation of sperm ( 25 ). Thus, there are multiple healthcare areas that could benefit from advances in the production of unique protease-biased chemical matter for inhibiting this important target class.…”
mentioning
confidence: 99%